Comparative Effectiveness of BNT162b2 and mRNA-1273 Booster Dose After BNT162b2 Primary Vaccination Against the Omicron Variants: A Retrospective Cohort Study Using Large-Scale Population-Based Registries in Japan. (18th September 2022) - Ono, Sachiko; Michihata, Nobuaki; Yamana, Hayato; Uemura, Kohei; Ono, Yosuke; Jo, Taisuke; Yasunaga, Hideo
Abstract: Background: Direct comparative effectiveness of booster doses of BNT162b2 and mRNA-1273 after BNT162b2 primary vaccination is unknown. Methods: We investigated comparative effectiveness of BNT162b2 and mRNA-1273 booster dose using data from registry systems for vaccination and coronavirus disease 2019 (COVID-19) infection in a local city in Japan. We followed participants aged ≥16 years who completed the BNT162b2 primary vaccination between 22 November 2021, and 15 April 2022. We collected information on age, sex, vaccination status, vaccine type, and infection status. Age was categorized as 16–44, 45–64, 65–84, and ≥85 years. Vaccine effectiveness for mRNA-1273 and no booster vaccination against BNT162b2 was estimated using age-stratified Cox regression adjusted for age, sex, and days since the second vaccination. The estimated hazard ratios for mRNA-1273 and no booster vaccinations were integrated separately using random effects meta-analyses. Results: During the study period, we identified 62 586 (40.4%), 51 490 (33.2%), and 40 849 (26.4%) participants who received BNT162b2, mRNA-1273, and no booster dose, respectively. The median age was 69, 71, and 47 years for BNT162b2, mRNA-1273, and no booster dose, respectively. The integrated hazard ratio with reference to BNT162b2 was 1.72 for no booster vaccination and 0.62 for mRNA-1273. The comparative effectiveness of mRNA-1273 was similar across age categories. Conclusions: Both homologous and heterologous vaccinations are effective against Omicron variants. In the head-to-head comparison, the effect was stronger in people who received heterologous vaccination than in those who received homologous vaccination. These findings may help improve logistics and decision making in future vaccination programs. Abstract : We conducted head-to-head comparison of vaccine effectiveness between BNT162b2 and mRNA-1273 for people who completed primary BNT162b2 course. When compared with BNT162b2 booster, mRNA-1273 booster dose was associated with significantly lower risk of coronavirus disease 2019 (COVID-19).